Metafuntional Meaning of the Ministary of Education and Research Policy on Education during the Pandemic: Functional Systematic Linguistic Study - Johar Amir; Ambo Dalle; Nur Qalbi Andini. A (Edumaspul: Jurnal Pendidikan, 2023)
The Indonesian government, through the Ministry of Education, Culture, Research and Technology (Kemendikbudristek), is trying to overcome the spread of the Covid-19 virus so that it does not spread further. In connection with this, the Ministry of Education and Culture has issued a circular letter from the Minister of Education and Culture regarding the implementation of education policies during the Covid-19 emergency period and a circular letter from the Secretary General of the Ministry of Education and Culture regarding guidelines for organizing learning during the emergency period. This research aims to reveal ideational meaning which includes expressive meaning and logical meaning. This research is a type of qualitative research. The data for this research are clauses that contain ideational meaning. The data source is quoted from a letter published by the Ministry of Education and Culture, Research and Technology regarding learning during the 2020-2021 pandemic. Data collection techniques are carried out through documentation techniques, reading techniques and note-taking techniques. The data analysis techniques include data reduction, data presentation, inference and verification. The findings of this research are ideational meaning which includes (1) experiential meaning, and (2) logical meaning. The experiential meaning is, (a) the meaning of the material process in the phrase wash your hands, get used to a clean lifestyle . This phrase means living clean, preventing viruses,(b) the mental process in the phrase knowing learning methods contains the meaning of understanding, and in the phrase getting used to a clean lifestyle contains the meaning of habituation, (c) verbal process of the phrase implementing health protocols and hopefully we can share with each other. The first verbal phrase contains the meaning of prevention, and helping each other in dealing with Covid 19, (d) the relational process in the phrase being an ambassador for change and implementing cough etiquette, both phrases contain the meaning of preventing virus transmission, (e) the behavioral process in the phrase avoiding physical contact and the phrase limiting guests. This phrase contains the meaning of keeping your distance. (2) Logical meaning, namely the use of conjunctions and, after, as long as, because, as, as, and before. Keywords: metafunctional meaning, ideational meaning of policy, education, pandemic times.